Characteristics and risk factors for spontaneous and postoperative consecutive exotropia in children with esotropia - Wen, Jing; Li, Ruiying; Li, Ruoshi; Li, Xiaoqing; Zhu, Dehai (Frontiers in Pediatrics, 2023)
Background: To investigate the risk factors for the development of consecutive exotropia (CXT) by comparing patients with spontaneous or postoperative CXT during follow-up with another group of patients who had no deviation or less than 10 prism dioptre (PD) esotropia. Methods: In this retrospective cohort study, 6 patients with spontaneous CXT (group A), 13 patients with postoperative CXT (group B), and 39 patients with no exotropia (group C) were enrolled. Probable risk factors for CXT were evaluated among the groups. Kruskal-Wallis H test was used to determine if any significant differences were present among the groups. Fisher’s exact test or Mann-Whitney U test was used for univariate analyses to compare differences between case groups or between case and control groups. The Bonferroni method was used to conduct multiple comparisons. Results: The follow-up period of spontaneous CXT patients was significantly longer than that of postoperative CXT and nonconsecutive exotropia patients (p = 0.035 and p < 0.001, respectively). The interval between alignment and CXT onset in spontaneous CXT patients was slightly longer than that in postoperative CXT patients, but not significantly difference (6.50 vs. 5.00 years, p = 0.072). Vertical deviation was associated with a high risk of postoperative CXT (p = 0.001). Most (38 [97.44%]) nonconsecutive exotropia patients had fusion; conversely, the absence of fusion function (p < 0.001) as well as stereoacuity (p = 0.029) were associated with a high risk of CXT. Conclusion: Vertical deviation and poor binocular function are strongly associated with a high risk of CXT. Children with spontaneous CXT are highly recommended to be followed-up long-term, while they maintain long-term ocular alignment before developing consecutive exotropia from comitant esotropia (CE).